Evaluation of Placental Transfer and Tissue Distribution of cis- and Trans-Permethrin in Pregnant Rats and Fetuses Using a Physiological-Based Pharmacokinetic Model - Personne, Stéphane; Brochot, Céline; Marcelo, Paulo; Corona, Aurélie; Desmots, Sophie; Robidel, Franck; Lecomte, Anthony; Bach, Véronique; Zeman, Florence (Frontiers in Pediatrics, 2021)
Biomonitoring studies have highlighted the exposure of pregnant women to pyrethroids based on the measurement of their metabolites in urine. Pyrethroids can cross the placental barrier and be distributed in the foetus as some pyrethroids were also measured in the meconium of newborns. Prenatal exposure to pyrethroids is suspected to alter the neurodevelopment of children, and animal studies have shown that early life exposure to permethrin, one of the most commonly used pyrethroid in household applications, can alter the brain development. This study aimed to characterize the fetal permethrin exposure throughout gestation in rats. We developed a pregnancy physiologically based pharmacokinetic (pPBPK) model that describes the maternal and fetal kinetics of the cis- and trans- isomers of permethrin during the whole gestation period. Pregnant Sprague-Dawley rats were daily exposed to permethrin (50 mg/kg) by oral route from the start of gestation to day 20. Permethrin isomers were quantified in feces, kidney, mammary gland, fat and placenta in dams and in both maternal and foetal blood, brain and liver. Cis and trans-permethrin were quantified in fetal blood and tissues with higher concentrations for the cis isomer. The pPBPK model was fitted to the toxicokinetic maternal and fetal data in a Bayesian framework. Several parameters were adjusted such as hepatic clearances, partition coefficients and intestinal absorption. Our work allowed to estimate the prenatal exposure to permethrin in rats, especially in the fetal brain and to quantitatively estimate the placental transfer. These transfers could be extrapolated to humans, and be incorporated in a human pPBPK model to estimate the fetal exposure to permethrin from biomonitoring data.